A Study of the Hydrochlorination Reactions of the Nickel Segregation Process - Webb I. D; Young D. R (The Australasian Institute of Mining and Metallurgy, 1987)
The hydro-chlorination of Fe2O3 and Fe304 has been investigated in the range 850-950¦C in order to elucidate the role of iron in the segregation process for nickeliferous laterites. The kinetics of Fe203 chlorination using 20% HC1 - 80% N2 gas mixtures is consistent with a single-stage structure control model, whereas Fe3O 4 exhibits a two-stage reaction mechanism. Oxygen potential measurements using a CSZ probe located above the bed and X-ray powder diffraction results confirm the proposed reaction scheme. When a serpentine nickeliferous laterite (1.03% Ni - 11.7% Fe) was chlorinated at 900¦C with a 20% HCl - 80% N2 gas mixture it was found that the iron oxide in the ore was extracted in a similar manner to the synthetic iron oxides. Also, it was found that the nickel extraction from the ore paralleled that of the iron and the tests indicated that for the major part of the extraction, the solid nickel species were in equilibrium with the gas phase. The recovery of nickel from laterite ores by the segregation process has been investigated by a number of workers and several extensive reviews of the literature associated with this field have been published (Iwasaki, 1972; Canterford, 1975; Wright, 1973).